(untitled) - Child, Lee (New York, 2013)
"Never go back--but Jack Reacher does, and the past finally catches up with him. Never Go Back is #1 New York Times bestselling author Lee Child's new novel of action-charged suspense starring "one of the best thriller characters at work today" (Newsweek). Former military cop Jack Reacher makes it all the way from snowbound South Dakota to his destination in northeastern Virginia, near Washington, D.C.: the headquarters of his old unit, the 110th MP. The old stone building is the closest thing to a home he ever had. Reacher is there to meet--in person--the new commanding officer, Major Susan Turner, so far just a warm, intriguing voice on the phone. But it isn't Turner behind the CO's desk. And Reacher is hit with two pieces of shocking news, one with serious criminal consequences, and one too personal to even think about. When threatened, you can run or fight. Reacher fights, aiming to find Turner and clear his name, barely a step ahead of the army, and the FBI, and the D.C. Metro police, and four unidentified thugs. Combining an intricate puzzle of a plot and an exciting chase for truth and justice, Lee Child puts Reacher through his paces--and makes him question who he is, what he's done, and the very future of his untethered life on the open road. Praise for #1 bestselling author Lee Child and his Jack Reacher series "Child is a superb craftsman of suspense."--Entertainment Weekly "The truth about Reacher gets better and better."--Janet Maslin, The New York Times"--
Booklist
Publishers Weekly
Kirkus Reviews
Library Journal Prepub Alert
Adult.
Adult.
Keywords: Fiction; Adventure fiction; Fiction; Mystery fiction; Criminal investigation; Reacher, Jack (Fictional character); Homicide; Fiction; Police; Fiction